Chemical analysis of Cyanobacterial fatty acids from Cagar Alam Pulau Dua, Banten: Insights from gas chromatography - Savitri, Lucia Dwi; Fitri, Siti Gia Syauqiyah; Khastini, Rida Oktorida (Biological Environment and Pollution, 2024)
Cyanobacteria exhibit a wide range of fatty acid profiles, which vary significantly among different species and strains. This study aimed to characterize the fatty acid profile of cyanobacteria isolated from Cagar Alam Pulau Dua (CPAD) Sanctuary in Serang, Banten. The isolates, previously identified as Lyngbya sp. and Aphanothece sp., were grown on ASN-III medium and harvested at the beginning of the stationary phase. Cyanobacterial lipids were extracted using two methods, i.e., the Bligh and Dyer method and the Soxhlet method. The composition of cyanobacterial fatty acid was analyzed using gas-liquid chromatography (GLC). The result showed that Lyngbya and Aphanothece have a higher saturated fatty acid composition than unsaturated fatty acid. Lyngbya contains 33.154% SFAs and 7.304% UFAs, while Aphanothece contains 55.172% SFAs and 44.783% UFAs. The saturated fatty acids in Lyngbya and Aphanothece are lauric acid, myristic acid, palmitic acid, and stearic acid, while the unsaturated fatty acids found are oleic acid and linoleic acid. The study paves the way for further research into the industrial applications of cyanobacterial fatty acids, particularly in biofuel production, nutraceuticals, and other biotechnological fields.